Peningkatan Motivasi Belajar Siswa Kelas VIII Melalui Layanan Bimbingan Kelompok - Amanda, Betania Cahya; Sutoyo, Anwar; Nusantoro, Eko (Universitas Negeri Semarang, 2013)
This study was conducted based on the phenomena that is in SMP 1 Semarang which indicates the level of students motivation is low. This study aims determine the level of success in overcoming the low learning motivation using group counseling.This type of research is action research guidance and counseling. Subjects were 8 from eighth grade students in SMP N 1 Semarang. Data collection tool used is the scale of learning motivation, observation, and interviews. The instrument has been tested for use in the study using the formula product moment validity and reliability with Alpha formula. The data analysis technique used is descriptive quantitative analysis with percentages and qualitative analysis.Results of research before obtaining treatment learning motivation is low at 44.4%, after the first cycle increased to 65% in the medium category, and after receiving the provision of the second cycle increased to 74% with the higher category. Based on the research that has been done, it can be concluded that an increase learning motivation significantly after organized group counseling